A Study of Psychological Atmosphere Phenomenon of Handball Teams and its Relation with their Achievement in Top Tournament in Palestine - Ramzy Jaber (My University, 2010)
This study aims at identifying the psychological atmosphere of handball teams and its relation. With their achievement in top tournament in Palestine according to the following variables: The playing center and the hand used. The study has been applied to a sample of (60) Top handball players, namely (40%) of the Target population estimated to (150) players. The researcher has employed a descriptive approach and the standard of psychological atmosphere required for sporting teams designed in (1998) to gather data and achieve the objectives of the study. The findings of the study have showed that the psychological atmosphere of handball teams is highly positive. Their response has reached (77.5%). The findings of the study have also indicated that there are no statistically significant differences in the psychological atmosphere of handball players and relation with their achievement in Top tournament in Palestine. This is due to the variables of the playing center and the hand used.